Factors affecting the adoption of sustainable tuna fishing practices: The case of municipal fishers in Maasim, Sarangani Province, Region 12, Philippines. (March 2017) - Digal, Larry N.; Placencia, Shemaiah Gail P.
Abstract: Tuna species, being one of the most marketable aquatic resources, have been facing severe threats towards overexploitation and depletion. Continuous increase in demand for tuna products has driven a hike in fishing pressure which led to the exhaustion of tuna stocks in the sea. With this, several measures have been made in order to uphold the sustainability of the methods employed in the extraction of tuna. Thus, this study attempts to identify the factors affecting the municipal fishers' adoption and non-adoption of sustainable tuna fishing practices in Region 12, Philippines, the most significant tuna producing region in the country. Employing logit regression, the fishers' household size, education, experience in fishing, the type of buyer, and effort days per fishing trip appeared to significantly affect the fishers' adoption decision. Interestingly, both private and government initiated incentives did not appear to affect their adoption decision, although the breadth of the recipients was not vast. Moreover, the estimated rate of adoption among municipal fishers was still seen to be low, despite the fishers' acknowledgement of the industry's potential collapse.